Advances in 3D Modeling: Preoperative Templating for Revision Wrist Surgery. (September 2017) - Osagie, Liza; Shaunak, Shalin; Murtaza, Aasim; Cerovac, Sonja; Umarji, Shamim
Background: Three-dimensional (3D) printing is a computer-directed process leading to the layered synthesis of scaled models. The popularity and availability of the technique has exponentially increased over the last decade, and as such is seeing a greater number of medical and surgical applications.Methods: We report 3 cases involving the use of 3D printing as an aid to operative planning in the revision of wrist surgery.Results: All patients underwent successful operative interventions with a £34 average cost of model creation.Conclusions: A growing number of reports are emerging in reconstructive surgical specialities including maxillofacial, orthopedic, and plastic surgery; from our experience, we advocate the economically viable use of 3D printing for preoperative templating.